IMPLEMENTASI METODA PRE-PROCESSING UNTUK MENINGKATKAN LAJU AKURASI HASIL KOMPUTASI OPERASI PENJUMLAHAN SEKUENSIAL MULTI OPERAND SISTEM WAKTU NYATA - Andrizal andrizal (Teknik Elektro Politeknik Negeri Padang, 2013)
Real-time system works in a limited period of time in accordance with the deadline time given. The success of a real time system performance is determined by several time components such as release time, processing time and time deadlines. Problems arise when the processing time is not enough due to the delay factor deadline or other factors, while the deadline time has come and the process had to be stopped. When the process is stopped, the results obtained have not been enough to be used as the end result of data systems fail to meet the given time constraint. There are several ways to overcome this, one is to perform preprocessing before the end of the process is done. In the sequential preprocessing system multioperand summation of the operand-operand which can be summed sort operand-operand which has significant influence on the results done first. When the process had to be stopped due to a deadline is coming then the accuracy of the results produced may be used as the final result. This study utilized the method as a preprocessing ascend in sorting systems to sort operand-operand values to be summed from largest to smallest. The results show the accuracy of the rate of change of the summation process in accordance with the needs of real-time system when the process had to be stopped before the end.